A 2-year follow-up study of patients participating in our transcranial pulsating electromagnetic fields augmentation in treatment-resistant depression. Issue 2 (13th January 2015) - Bech, Per; Lindberg, Lone; Straasø, Birgit; Larsen, Erik Roj
Abstract : Objective: We have made a 2-year follow-up study to evaluate the effect of repeated transcranial pulsating electromagnetic fields (T-PEMF) augmentation in patients who had achieved remission but later on relapsed, as well as to identify factors contributing to treatment-resistant depression in patients who did not respond to T-PEMF. Methods: Using the Longitudinal Expert Assessment of All Data approach the patients were classified in four groups: A: patients who achieved remission; B: patients with doubtful effect; C: patients with no effect; and D: patients who were hard-to-assess. Results: In group A, comprising 27 patients, 13 had relapsed; they obtained a clear remission after a repeated course of T-PEMF augmentation. In group D, comprising 16 patients, we identified misdiagnostic factors both concerning the event of remission after the previous T-PEMF augmentation and concerning the aetiology (psychosocial stressors and co-morbid conditions). Compared with the other groups, the group D patients had a smaller number of previous episodes ( p =0.09) and a longer duration of the current episode ( p =0.01). Conclusion: T-PEMF has an effect among patients who relapsed after remission with the first series of T-PEMF. Treatment-resistant depression is a condition that has a high degree of multivariate problems. Misuse of alcohol or drugs, severe somatic disorders and other psychosocial problems may need other kinds of treatment before T-PEMF augmentation.